The Effective Symptoms Of COVID-19 Infection In Hadhramout Yemen, Comparative Study - Al-Akabari, Shouqi Abdullah; Hamed Baras, Maryam; Al-Afifi, Tahani Aidroos; Bin-Hameed, Eidha Ali (Enhanced Knowledge in Sciences and Technology, 2022)
COVID-19 is evolving rapidly worldwide. Many researches has been established to study the disease from different aspects to understand it well and control its prevalence. So, this study aimed to detect the major symptoms and the kind of the infection in the body to have a clear vision of the infection of the virus based also on other future investigations. Our results suggested that the mean age of the positive COVID-19 patients was 55.16 years old and it was significantly associated with COVID-19 infection (P value = 0.001). Also, infected COVID-19 males patients were higher than females 74.9% with statistically significant value (P value= 0.018). However, all studied risk factors in this study haven’t been significantly associated with the infection, but fever, cough and shortness of breath were the most common symptoms in COVID-19 patients with high rates of 92.45, 88.6% and 80.6% respectively. In brief, Gender males and older age were the significant risk factors associated with infection of COVID-19. These results provide references for clinical judgment and early intervention, and may be beneficial to our overall understanding of COVID-19.